The Effects of Calcium, Vitamins D and K co-Supplementation on Markers of Insulin Metabolism and Lipid Profiles in Vitamin D-Deficient Women with Polycystic Ovary Syndrome - Karamali, Maryam; Ashrafi, Mahnaz; Razavi, Maryamalsadat; Jamilian, Mehri; Akbari, Maryam; Asemi, Zatollah (Experimental and Clinical Endocrinology & Diabetes, 2017)
Data on the effects of calcium, vitamins D and K co-supplementation on markers of insulin metabolism and lipid profiles among vitamin D-deficient women with polycystic ovary syndrome (PCOS) are scarce. This study was done to determine the effects of calcium, vitamins D and K co-supplementation on markers of insulin metabolism and lipid profiles in vitamin D-deficient women with PCOS. This randomized double-blind, placebo-controlled trial was conducted among 55 vitamin D-deficient women diagnosed with PCOS aged 18–40 years old. Subjects were randomly assigned into 2 groups to intake either 500 mg calcium, 200 IU vitamin D and 90 µg vitamin K supplements (n=28) or placebo (n=27) twice a day for 8 weeks. After the 8-week intervention, compared with the placebo, joint calcium, vitamins D and K supplementation resulted in significant decreases in serum insulin concentrations (−1.9±3.5 vs. +1.8±6.6 µIU/mL, P=0.01), homeostasis model of assessment-estimated insulin resistance (−0.4±0.7 vs. +0.4±1.4, P=0.01), homeostasis model of assessment-estimated b cell function (−7.9±14.7 vs. +7.0±30.3, P=0.02) and a significant increase in quantitative insulin sensitivity check index (+0.01±0.01 vs. −0.008±0.03, P=0.01). In addition, significant decreases in serum triglycerides (−23.4±71.3 vs. +9.9±39.5 mg/dL, P=0.03) and VLDL-cholesterol levels (−4.7±14.3 vs. +2.0±7.9 mg/dL, P=0.03) was observed following supplementation with combined calcium, vitamins D and K compared with the placebo. Overall, calcium, vitamins D and K co-supplementation for 8 weeks among vitamin D-deficient women with PCOS had beneficial effects on markers of insulin metabolism, serum triglycerides and VLDL-cholesterol levels.
Keywords: supplementation; polycystic ovary syndrome; insulin metabolism; lipid profiles